PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PT SETYA KULINER MANDIRI JAGAKARSA JAKARTA SELATAN - Aan Rahman; Puji Yuniarti; Dinda Aprilia (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2020)
One of the important activities business was service quality which is must be realized and main prioritized by the organization. This research studied the influence of service quality to customer satisfaction in D’Besto Restaurant in Jagakarsa South Jakarta. Services of the employee are business activities that result was not a product in a physical form or construction which is one of the factors that affect customer satisfaction. The main purpose of this research is to analyze the quality service of employees influenced by customer satisfaction. This research uses the descriptive quantitative method and the sample in this study amounted to 80 respondents taken through the incidental sampling technique. While the data collection method uses observation, interviews, and questionnaires. Data analysis used is a simple linear regression model of ordinary least square (OLS) with a significance level of 5%. The results of the study with the correlation coefficient (r) are 0,828 showed that the variable of service quality significantly affects the customer satisfaction. The influence of dependent variables (service quality) similarly gave significant influence towards the customer satisfaction percentage of 68,6% and the remaining 31,4% is affected by the other variables. Based on the result improves that by increasing the quality of the service, the employee service functions more effective, efficient, and gives more satisfaction to the customer.